Role of cardiac β1-adrenergic and A1-adenosine receptors in severe arrhythmias related to Parkinson’s disease - Menezes-Rodrigues, Francisco Sandro; Oliveira, Marcelo Pires de; Araújo, Erisvaldo Amarante; Ferraz, Henrique Ballalai; Finsterer, Josef; Olszewer, Efrain; Taha, Murched Omar; Scorza, Carla Alessandra; Caricati-Neto, Afonso; Scorza, Fúlvio Alexandre (Clinics, 2024)
Aims:Although reduced life expectancy in Parkinson's Disease (PD) patients has been related to severe cardiac arrhythmias due to autonomic dysfunctions, its molecular mechanisms remain unclear. To investigate the role of cardiac β1-Adrenergic (β1AR) and A1-Adenosine (A1R) receptors in these dysfunctions, the pharmacological effects of stimulation of cardiac β1AR (isoproterenol, ISO), in the absence and presence of cardiac β1AR (atenolol, AT) or A1R (1,3-dipropyl-8-cyclopentyl xanthine, DPCPX) blockade, on the arrhythmias induced by Ischemia/Reperfusion (CIR) in an animal PD model were studied. Methods: PD was produced by dopaminergic lesions (confirmed by immunohistochemistry analysis) caused by the injection of 6-hydroxydopamine (6-OHDA, 6 μg) in rat striatum. CIR was produced by a surgical interruption for 10 min followed by reestablishment of blood circulation in the descendent left coronary artery. On the incidence of CIR-Induced Ventricular Arrhythmias (VA), Atrioventricular Block (AVB), and Lethality (LET), evaluated by Electrocardiogram (ECG) analysis, the effects of intravenous treatment with ISO, AT and DPCPX (before CIR) were studied. Results: VA, AVB and LET incidences were significantly higher in 6-OHDA (83%, 92%, 100%, respectively) than in control rats (58%, 67% and 67%, respectively). ISO treatment significantly reduced these incidences in 6-OHDA (33%, 33% and 42%, respectively) and control rats (25%, 25%, 33%, respectively), indicating that stimulation of cardiac β1AR induced cardioprotection. This response was prevented by pretreatment with AT and DPCPX, confirming the involvement of cardiac β1AR and A1R. Conclusion:Pharmacological modulation of cardiac β1AR and A1R could be a potential therapeutic strategy to reduce severe arrhythmias and increase life expectancy in PD patients.